Nilai Moderasi Beragama dalam Tradisi Pernikahan Suku Linggau - Zainuri; Asnaini; Sirajuddin (Kartika: Jurnal Studi Keislaman, 2026)
Discourse on religious moderation in Indonesia remains predominantly shaped by normative policy frameworks and textual analyses, often overlooking customary rituals as lived mechanisms that sustain social harmony. This study identifies and maps the values of religious moderation institutionalized within the marriage traditions of the Linggau tribe. Employing a qualitative ethnographic design, data were gathered through participant observation, in-depth interviews, and document analysis with customary elders, religious figures, and ritual practitioners, and analyzed thematically. Findings demonstrate that the Basindo, Ngulang Rasan, Ngantat Dendan, Akad Nikah, Hari Masak, Mapak Sedekah, and Deker stages systematically embody balance (tawassuth), procedural justice (i’tidal), active tolerance (tasamuh), communal solidarity, and contextual spirituality. These values are transmitted intergenerationally as cultural habitus, adapt to modernity, and culturally counteract puritanical homogenization. The study concludes that religious moderation operates as an organic, culturally grounded practice rather than a top-down policy construct. Theoretically, it advances the lived religion paradigm; practically, it advocates embedding local wisdom into multicultural curricula and dynamic heritage preservation frameworks